Reviewing the nature and effects of confessions conflict - سعید ابراهیمی (مطالعات فقه و حقوق اسلامی, 2016)
Of course, it is obvious confession to murder is such arguments that prove a murder case. However, in some cases where someone has confessed to committing the murder and on the same subject, the other one confesses for intentional murder, pure or quasi-intentional error. There are different views among Jurists concerning the ruling on this case. The famous jurisprudence theory that reflected in Article 75 of Act 235 maintains that discretionary for parents of murdered in reference to each of the participants to confess and act according to the provisions admitted. In the present article the writer first criticizes the promise of discretionary along with criticizing and reviewing documentation of the famous theory and prejudicing about them and accepts to refer to other reasons and the expertise theory on the basis of the principle of conflict and portioning two or more confession and in some cases provisions of the rule of voting. Second, discretionary sentence prescribed in the provisions of Article 477 approved in 1392 requires to revise. Third it is believed that examples of occurring conflicts are not limited to assumptions recognized by jurists.